Methicillin resistant Staphylococcus epidermidis. - Haque, N; Bari, MS; Haque, N; Khan, RA; Haque, S; Kabir, MR; Yasmin, T (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 326-331 The abstract of this article is available on the PubMed website